2020
DOI: 10.1016/j.bcp.2020.113982
|View full text |Cite
|
Sign up to set email alerts
|

The seafood Musculus senhousei shows anti-influenza A virus activity by targeting virion envelope lipids

Abstract: The seafood Musculus senhousei shows anti-influenza A virus activity by targeting virion envelope lipids, Biochemical Pharmacology (2020), doi: https://doi. AbstractMarine environments are known to be a new source of structurally diverse bioactive molecules. In this paper, we identified a porphyrin derivative of Pyropheophorbide a (PPa) from the mussel Musculus senhousei (M. senhousei) that showed broad anti-influenza A virus activity in vitro against a panel of influenza A viral strains. The analysis of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…S1C). This conclusion is consistent with the results of our previous study, showing that the antiviral activity of Pyropheophorbide a (PPa) was due to the interaction with the viral membrane or biophysical interference with the virus-cell membrane fusion process, which resulted in blocking the entry of an enveloped virus into cells (17).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…S1C). This conclusion is consistent with the results of our previous study, showing that the antiviral activity of Pyropheophorbide a (PPa) was due to the interaction with the viral membrane or biophysical interference with the virus-cell membrane fusion process, which resulted in blocking the entry of an enveloped virus into cells (17).…”
Section: Discussionsupporting
confidence: 93%
“…The biological activity test showed that PPa exhibited good antiviral activity against a panel of influenza A viruses. The mechanism of action study indicated that PPa exerted its inhibitory effect in the early stage of virus infection by interacting with the lipid bilayer function of the virion, blocking the entry of enveloped viruses into host cells (17).…”
Section: Introductionmentioning
confidence: 99%
“…However, pyroPba was also more toxic, and hence the final selectivity index was not higher than that of Pba. PyroPba has already been demonstrated to be active against IAV, RSV (respiratory syncytial virus), and SARS-CoV-2 ( 41 ) . The authors studied the mechanism of action of pyroPba against IAV and showed that the molecule targets the membrane of the virus and not the surface glycoproteins, a mechanism which is consistent with the one that we observed for Pba in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The authors studied the mechanism of action of pyroPba against IAV and showed that the molecule targets the membrane of the virus and not the surface glycoproteins, a mechanism which is consistent with the one that we observed for Pba in our study. A requirement for photo-activation of pyroPba was not investigated nor mentioned by Chen et al ( 41 ) . Porphyrins have already been described for their antiviral activity ( 25 , 42 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PA is reported to have antiwrinkle activity in UV-stimulated skin tissue through suppression of MMP-1 and MMP-3 expression (Granted patent: US 20170189292). Pyropheophorbide a (PyroPA), a decarboxylated derivative of PA, has been reported to inhibit the growth of hepatitis C virus [ 18 ] and influenza A [ 29 ]. PyroPA and pyropheophorbide a methyl ester (PyroPA-ME), based on its photosensitizing characteristics, can also be applied in anticancer PDT [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%